Microwave-assisted synthesis of ZnO nanostructure flowers - Anukorn Phuruangrat (2018)
Hexagonal ZnO nanostructure flowers were successfully synthesized from a 1:15 molar ratio of Zn(CH3COO)2{radical dot}2H2O to KOH using 180 W microwave radiation for 20 min. The product phase was detected using X-ray diffraction (XRD) and selected area electron diffraction (SAED). A diffraction pattern was also simulated and was found to be in accordance with those of the experiment and the JCPDS database. Raman spectrometry revealed the presence of four vibration peaks at 337.85, 381.13, 437.54 and 583.30 cm- 1. The product, spear-shaped nanorods in flower-like clusters, was characterized using both scanning electron microscopy (SEM) and transmission electron microscopy (TEM). High resolution TEM (HRTEM) showed that growth of the spear-shaped nanorods was in the [001] direction, which was normal to the (002) planes composing a lattice fringe of the nanorods. A formation mechanism of hexagonal ZnO nanostructure flowers was also proposed. © 2009 Elsevier B.V. All rights reserved.